2021
DOI: 10.4103/jisp.jisp_40_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aloe vera as a local drug delivery agent in the management of periodontal diseases: A systematic review and meta-analysis

Abstract: Background: Aim of the present meta-analysis was to evaluate the effect of Aloe vera in various forms such as gel, mouthwash, and dentifrice on gingival and plaque index (PI) in comparison to various allopathic products such as chlorhexidine, metformin, chlorine dioxide, fluoridated toothpaste, and alendronate. Materials and Methods: A comprehensive electronic search was conducted on PubMed/MEDLINE, GOOGLE SCHOLAR, and HAND SEARCH of reference list of archived articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Aloe vera gel contains various bioactive components, including polysaccharides, anthraquinones, vitamins, minerals, and enzymes [23,30]. Furthermore, aloe vera components can inhibit the production of inflammatory cytokines and nitric oxide [31,32]. It stimulates fibroblast proliferation and collagen synthesis, possibly aiding tissue repair and regeneration [32].…”
Section: Aloe Vera (Aloe Barbadensis)mentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe vera gel contains various bioactive components, including polysaccharides, anthraquinones, vitamins, minerals, and enzymes [23,30]. Furthermore, aloe vera components can inhibit the production of inflammatory cytokines and nitric oxide [31,32]. It stimulates fibroblast proliferation and collagen synthesis, possibly aiding tissue repair and regeneration [32].…”
Section: Aloe Vera (Aloe Barbadensis)mentioning
confidence: 99%
“…Furthermore, aloe vera components can inhibit the production of inflammatory cytokines and nitric oxide [31,32]. It stimulates fibroblast proliferation and collagen synthesis, possibly aiding tissue repair and regeneration [32]. Aloe Vera mouthwash has been reported to have comparable effects to chlorhexidine in many studies regarding plaque index without causing tooth discoloration and taste alterations, which are frequently associated with chlorhexidine [30,[33][34][35].…”
Section: Aloe Vera (Aloe Barbadensis)mentioning
confidence: 99%
“…Aloe vera (AV) is a perennial succulent commonly used for healing due to its pharmacological and therapeutic properties [22,23]. Balcik and Koral [24] reported that AV had degradable and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%